The creation of the Cenecistas Schools in Brazil: a historical approach (Research, Society and Development, 2018)
The National Campaign for Community Schools (CNEC) is an institution that has a significant presence in Brazilian education and educational policy. Thus, we propose to research and analyze the history of the CNEC, which began as the Ginasiano Pobre (CGP) Campaign in Recife (PE) in the year 1943. The research is documental and bibliographic. The documentary corpus is composed of activity reports, institutional publications of CNEC. The understanding of community development, non-formal education, and history of educational institutions guide our analysis of the history of the National Community School Campaign. The movement for the creation of the CGP originated in Brazil inspired by the experience of Victor Raul Haya de La Torre, with the creation of the Popular Universities González Prada in the early 1920s in Peru. Felipe Tiago Gomes was the main protagonist and founder of the Campaign, which, along with other university colleagues, decided to prepare students lacking resources to continue their studies, in addition to primary education. After founding the first Gymnasium, they decided to expand throughout Brazil and arrived in Rio Grande do Norte in October 1948. The CNEC took a one-way speech between the public and private, between the State and the Market, based , for both, in the mechanism and in the discourse of the community theme, a model where the people of the community themselves were in charge of administering the Institution.